Bernardo Bátiz-Lazo. Cash and Dash: How ATMs and Computers Changed Banking. Oxford: Oxford University Press, 2018, XIV, 324 pp. ISBN: 9780198782810. - Del Ángel, Gustavo A. (Investigaciones de Historia Económica, 2020)
Sin resumen